2007
DOI: 10.1071/ah070231
|View full text |Cite
|
Sign up to set email alerts
|

The role of practice nurses in coordinated care of people with chronic and complex conditions

Abstract: General practice in Australia must cope with growing numbers of individuals with chronic and complex needs. The Australian Government has recognised the need to reform the primary health care sector to address this issue, with recent initiatives, such as coordinated care. The overall goal of coordinated care at a national level is to facilitate integrated care for people with chronic and complex conditions, by enhancing collaborative partnerships among general practitioners, primary health care providers, comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This finding is somewhat unexpected given the relative volume of services used by people with complex health needs, the emphasis on primary care as the main point of contact with the health system and in the management of people with chronic and complex conditions, and the fact that the Australian Government has introduced several funding programs to support and encourage GP management of people with chronic and complex disease. [15][16][17] It should be noted that crude attendance rates indicate that GPs do indeed have significant contact with people with complex needs; it is just that after adjustment for confounders, this contact is no greater than for people without a complex condition. It has also been observed that although GPs are heavily involved in providing care to people with chronic illness, they provide the majority of care to those whose illness is mild to moderately severe.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is somewhat unexpected given the relative volume of services used by people with complex health needs, the emphasis on primary care as the main point of contact with the health system and in the management of people with chronic and complex conditions, and the fact that the Australian Government has introduced several funding programs to support and encourage GP management of people with chronic and complex disease. [15][16][17] It should be noted that crude attendance rates indicate that GPs do indeed have significant contact with people with complex needs; it is just that after adjustment for confounders, this contact is no greater than for people without a complex condition. It has also been observed that although GPs are heavily involved in providing care to people with chronic illness, they provide the majority of care to those whose illness is mild to moderately severe.…”
Section: Discussionmentioning
confidence: 99%
“…Rebates only apply to a small range of activities including immunisation, wound care, pap smears and chronic disease prevention and management activities (Patterson et al . ). Recent changes to the Medicare Act have also extended the capacity to apply for MBS provider numbers to nurse practitioners and midwives (Department of Health & Ageing , Harvey , Lane ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the Practice Nurse Incentives programme, funding has been targeted towards employment of PNs in rural settings and training and support schemes (Patterson et al . ). There has been accompanying growth of nursing employment in primary care and in particular, within general practice.…”
Section: Introductionmentioning
confidence: 97%
“…(13) In Australia, both the National Health and Hospitals Reform Funding is also a major barrier to practice nurses taking on a care co-ordination role. (38) Although specific funding for some practice nurse activities has been introduced through Medicare (e.g. development of care plans), care co-ordination for complex patients is not supported.…”
Section: Discussionmentioning
confidence: 99%
“…(21,22,(38)(39)(40) A COPD care co-ordinator should be pro-active, supporting as much independence as possible through education and assistance with problem solving, but also have the skills and capacity to intervene with more specific assistance when needed. Such aThis advanced practice role should combine the skills of a palliative approach, with those specific to COPD, e.g.…”
Section: Scope Of the Rolementioning
confidence: 99%